Ginsenoside Rb1 Produces Antidepressant-Like Effects in a Chronic Social Defeat Stress Model of Depression Through the BDNF–Trkb Signaling Pathway - Jiang, Ning; Huang, Hong; Zhang, Yiwen; Lv, Jingwei; Wang, Qiong; He, Qinghu; Liu, Xinmin (Frontiers in Pharmacology, 2021)
Ginsenoside Rb1 (Rb1), an important bioactive ingredient of Panax ginseng, has potent neuroprotective effects. The objective of the study is to elucidate the impact of Rb1 treatment on chronic social defeat stress (CSDS)–induced depressive-like behaviors and its related mechanism. According to the obtained results, the daily oral administration of Rb1 (35 and 70 mg/kg) and imipramine (15 mg/kg) for 28 days significantly reversed the social avoidance behavior, anhedonia, and behavioral despair via CSDS exposure, as demonstrated by the considerable elevation in the time in the zone in the social interaction test, consumption of sucrose solution in the sucrose preference test, and decrease in immobility time in the forced swim test. Moreover, Rb1 obviously restored the CSDS-induced decrease in the BDNF signaling pathway and hippocampal neurogenesis. Rb1 significantly increased the hippocampal levels of ERK, AKT, and CREB phosphorylation and increased the number of DCX+ cells in DG. Importantly, the antidepressant effects of Rb1 were completely blocked in mice by using K252a (the nonselective tyrosine kinase B inhibitor). In conclusion, our results indicated that Rb1 exerts promising antidepressant-like effects in mice with CSDS-induced depression, and its effects were facilitated by enhancing the BDNF signaling cascade and upregulation of hippocampal neurogenesis.